1998
DOI: 10.1146/annurev.ento.43.1.395
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Management of Hazelnut Pests

Abstract: Insect and mite pests cause serious damage to the hazelnut crop worldwide. The control strategies used against these pests include application of insecticides, classical and augmentative biological control, utilization of resistant varieties, and use of Bacillus thuringiensis-based preparations. In the United States, extensive research has been directed toward elucidating ecological interactions among different pests and natural enemies and understanding the role of abiotic factors in pest population dynamics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 51 publications
0
34
0
3
Order By: Relevance
“…A complex of pests causes damage on hazelnuts in North America, Europe and Turkey (Aliniazee, 1999). Even though Turkey places on the top of the list among all the countries producing hazelnut in hazelnut production and exportation, it is way back of many of them in terms of product harvested per unit field.…”
Section: Introductionmentioning
confidence: 99%
“…A complex of pests causes damage on hazelnuts in North America, Europe and Turkey (Aliniazee, 1999). Even though Turkey places on the top of the list among all the countries producing hazelnut in hazelnut production and exportation, it is way back of many of them in terms of product harvested per unit field.…”
Section: Introductionmentioning
confidence: 99%
“…1, Table 1). The average length of the forewing was determined to be 10 ± 0.8 mm for the female, and 9.3±0.3 for the male insects (Table 1), AliNiazee (1998) found that the adults were greyish red in colour, rostrum was slander, strongly curved and longer than body in the female, shorter than body in the male. The existence of adults starts in mid-March and the maximum density is reached in mid-May, depending temperature.…”
Section: Resultsmentioning
confidence: 97%
“…However, when the temperature rises the 16EC, they start flying long distances. Adults of has beetle moved towards different plants for feeding later adults which were laying migrated on the fruits that were not yet mature According to literature knowledge, the adults feed on hazelnut and on the fruits of various trees such as pear, peach, more rarely apple, plum and cherry (Ural et al, 1973;Paparatti, 1990;AliNiazee, 1998). Starting from early June, the eggs which were collected, measured, and photographed, They were conical and transparent, and 0.795 ± 0.14 x 0.525 ± 0.11 mm in size and, average (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of August the larvae emerge from the nuts and burrow into the ground, where this insect spends a wintering diapause (Akça & Tuncer, 2005). The weevil life cycle can last for 2 years, including overwintering larval and adult stages (Coutin, 1992;AliNiazee, 1998;Bel-Venner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%